2014
DOI: 10.1177/0049475514562492
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment practices among patients attending an Animal Bite Management clinic at a primary health centre in Haryana, North India

Abstract: A cross-sectional study was carried out at the Animal Bite Management (ABM) clinic in a primary health centre in the Faridabad district of Haryana. Information about socio-demographic characteristics, animal bite exposure and pre-treatment practices was obtained. Clinical examination determined the severity of the bite. All 619 patients who reported to the ABM clinic during January 2011 to December 2012 were included. Out of the total, 38% had applied chilli-oil paste, and 4% antiseptics to the wound as pre-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…In the current study, we found that more than four-fifths of animal bite victims applied no or inappropriate wound treatment, and similar findings have been reported in other national and international research [19, 34, 35]. Our analysis revealed that, most (66.6%) respondents could have an access to the RPC within 30 minutes, and nearly all victims (96.8%) could visit the RPC within 90 minutes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, we found that more than four-fifths of animal bite victims applied no or inappropriate wound treatment, and similar findings have been reported in other national and international research [19, 34, 35]. Our analysis revealed that, most (66.6%) respondents could have an access to the RPC within 30 minutes, and nearly all victims (96.8%) could visit the RPC within 90 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…Mucheru [51] reported that people with adequate rabies knowledge were more likely to perform proper health seeking practices (OR = 3.0, 95% CI = 1.4–6.8). The general public should be made aware of vaccination programs, timely PEP and proper wound treatment [35, 52]. Therefore, it is of utmost importance that public awareness is raised about the timely administration of proper PEP [53], which is in line with the theme of the year 2016 World Rabies Day “Educate, Vaccinate, Eliminate”.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in the studies by Wadde et al, Salve et al and Dhaduk et al in which 71.39%, 70.4% and 75% of the study participants were males respectively. 9,10,11 Majority of the study participants were males in all these studies which might be due to the reason that males have increased outdoor activity, mobility and hence have increased risk of exposure to bite. In the present study, majority of the study participants (90.8%) were Hindus while (9.2%) were Muslims.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Traditional methods lead to delay in seeking proper medical management of the dog bite wound. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%